Meme Splicing Genesis 6:1-4 and the Apocalypse of 2012 - Thomas, Paul (2012)
: In the morass that has become year 2012 apocalyptic thought, there has emerged a group of authors who are linking the year 2012, Genesis 6:1-4, and cultural fears concerning genetic engineering. This article examines the manner in which various authors combine these seemingly disparate threads to argue that Genesis 6:1-4 is a record of devious ancient genetic engineering and that the Bible foretells a time when similar events will herald the coming apocalypse, thought by some to coincide with the year 2012. Looking at this literature as representative of a type of improvisational millennialism, this article examines the rhetorical devices used to make this argument.
Keywords: Bibel; Apocalypse; Millennialism; Premillennialism; 2012; Genesis; Cloning; Nephilim; Conspiracy; improvisational; sons of God; genetic science